What is a vaccine? - Melissa K. Jones; Meghan A. Berryman; Kelley Lobean McKinley; Jennifer C. Drew (EDIS)
This publication discusses the purpose of a vaccine, clarifies a few important definitions, and describes the types of vaccines currently available. Written by Melissa K. Jones, Meghan A. Berryman, Kelley Lobean McKinley, and Jennifer C. Drew, and published by the UF/IFAS Department of Microbiology and Cell Science, May 2022.